(untitled) (Bangladesh Journal of Botany, 2014)
Phenology, floral and pollen morphological features and seed yield were studied in Indigofera tinctoria L. and I. suffruticosa Mill. Indigofera tinctoria bloomed three times i.e., mid-July, mid-August and early October during the study period. But I. suffruticosa bloomed only once i.e., in early September. The number of flowers/raceme and pods/raceme were higher in I. suffruticosa than those in I. tinctoria. However, the number of seeds/pod, seed size, 1000-seed weight and seed yield were higher in I. tinctoria. Pollen with auriculae near the aperture in Indigofera is being reported here for the first time. Size and exine thickness of pollen grains were higher in I. tinctoria than in I. suffruticosa. The highest number of flowers/raceme and seeds/plant were produced at the second flush in I. tinctoria. Therefore, I. tinctoria plants may be harvested after the maturity of pods from second flush for higher seed yield. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18024 Bangladesh J. Bot. 42(2): 231-237, 2013 (December